Análisis de optimización de tiempos y movimientos del trabajador en los procesos florícolas de la empresa Abril Flowers - Armijos Toapanta, Leoncio Bolívar (2022)
The objective of this research project is to conduct a study of times and movements in the production processes in the post-harvest area of the Abril Flowers; flower farm located in the province of Cotopaxi, in order to analyze the factors, elements or components that generate delays in work activities. The research was structured in two stages which helped us to generate a sequential and logical organization and distribution, to obtain data that show the standard time of the work done in each process. In the first stage of the project, the study of times and movements in the current production process was proposed, resulting in a production time of 71.50 minutes, taking into account each of the factors that may affect the proper development of production. For the second stage of the research project, an improvement of the process is suggested through the restructuring and reorganization of each activity, thus reducing the production time by 55.33 minutes in each of the activities developed by the workers, improving and increasing the daily production by 29.16%. A simulation process was carried out validating the values obtained in the analytical calculation between the current production process and the proposed process, these improvements can be implemented if a good organization and assignment of activities to workers is carried out, improving productivity in the company, in addition to improving the work environment.